REVALENCE OF BACKACHE AMONG SCHOOL GOING CHILDREN OF HYDERABAD SINDH (International Journal of Physiotherapy, 2016)
Background: The prevalence of backache is increasing in children with heavy weighed school bags and abnormal sitting posture both, at home and school. The aim of this study was to determine the prevalence of this much avoided issue of back pain among school going children of Hyderabad, Sindh.Methodology: 240 pupils (range, 7-14 years old) were recruited in their respective schools of Hyderabad city. Inclusions were all the present students on that particular day of data collecting and excluding those who were absent that day. A preformed questionnaire form was filled with all due consent, following which, examination was done to check the parameters of height, weight, BMI, weight of school bag, and posture analysis.Result: The prevalence of back pain was 46.7% among the total 240 subjects studied. Out of which 14.4% boys and 32.3% girls were affected. The majority of affected children were age group of 10-12 years old. In our study 61% children had school bags weighing around 5 kg, which is point to be considered by high officials of Primary Education System in Pakistan.Conclusion: The symptoms of backache were significantly visible in those students carrying heavy bags in proportion to their own weight and BMI. This was also closely related to the time duration, subjects were spending in front of computer/television. After analysis and all, it turned out that a significant number of students were affected by abnormal postures leading to backache-, which may be held equally responsible for further Alleviation of such symptoms later in life.